Enhancing Speaking Skills through Guessing Games: A Study on Descriptive Texts at SMP Sunan Ampel Porong - Makarim, Muhammad Nabil (English Language and Literature in Education Journal, 2024)
This study explores the implementation and student responses to integrating guessing games for teaching speaking skills through descriptive texts at SMP Sunan Ampel Porong during the 2018/2019 academic year. Employing a descriptive qualitative approach, the research focused on 7th-grade students. Data were gathered from observations and student responses via questionnaire, with the researcher serving as the primary instrument supported by observation field-notes, checklists, and questionnaires. The findings underscored several significant outcomes: firstly, the guessing game effectively heightened student engagement by fostering a lively learning atmosphere. Secondly, it notably encouraged students to actively participate in English speaking activities, demonstrating an increase in language use and confidence. Thirdly, teachers found the game to be a useful tool for maintaining classroom discipline and managing student behavior. In terms of student feedback, a majority expressed enthusiasm for the guessing game, citing it as both motivating and enjoyable. The implications drawn from these findings are manifold: educators are encouraged to diversify their teaching methodologies to sustain student interest and active involvement in lessons. Students are advised to take a more proactive role in their learning journey, capitalizing on engaging activities like guessing games to enhance language proficiency. Additionally, future research endeavors could explore further applications of guessing games across different facets of English language learning. Overall, this study underscores the potential of guessing games as an effective pedagogical tool for enhancing speaking skills and enriching the educational experience in language classrooms.